Synthesis and characterization of comb-like copolymers based on poly(ε-caprolactone) and poly(α-olefin) - Kinder, Sabina; Komber, Hartmut; Jehnichen, Dieter; Haeussler, Liane; Boehme, Frank; Garaleh, Mazen; Pospiech, Doris; Voit, Brigitte; Schulze, Ulrich (Macromolecular Chemistry and Physics, 2014)
Comb-like copolymers based on a polyolefin backbone of poly(10-undecene-1- ol) (PUol) with poly(ε-caprolactone) (PCL) side chains are synthesized in two steps. After synthesis of PUol by metallocene-catalyzed polymerization, the side-chain hydroxyl functionalities of this polar polyolefin are used as an initiator for the ring-opening polymerization (ROP) of ε-caprolactone (CL). In this context, copolymers with different lengths of PCL grafts are prepared. The chemical structure and the composition of the synthesized copolymers are characterized by 1H and 13C NMR spectroscopy. It is shown that the hydroxyl end groups of PUol act effectively as initiating sites for the CL ROP. Size-exclusion chromatography (SEC) measurements confirm the absence of non-attached PCL and the expected increase in molar mass after grafting. The thermal and decomposition behaviors are investigated by DSC and thermogravimetric analysis (TGA). The effect of the length of the PCL grafts on the crystallization behavior of the comb-like copolymers is investigated by DSC and wide-angle X-ray scattering (WAXS). © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: comb-like copolymers; metallocene catalysts; poly(10-undecene-1-ol); poly(ε-caprolactone); ring-opening polymerization